2021
DOI: 10.1039/d1gc00623a
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted hydrothermal treatments for biomass valorisation: a critical review

Abstract: The sustainable conversion of biomass into biofuels, chemicals and biomaterials has gained increasing attention to ensure the well-being of present and future generations. Among the different technologies available to date...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 180 publications
(281 reference statements)
1
45
0
Order By: Relevance
“…On the other hand, the detected conversion of glycerol was quite low (6.5% at 0.17 h) when conventional heating was selected as the energy supply method, and it climbed to 47.3% within 1.5 h and further increased to 72.8% when the reaction was prolonged to 6 h. These results indicated that microwave irradiation could shorten the reaction time greatly, which might be ascribed to microwave irradiation having higher thermal efficiency thanks to the interaction between the oscillating electromagnetic field of microwave and the dipoles of polar molecules. However, a conventional heating method can only provide heat to the reaction mixture via thermal conduction, and this conduction depends strongly on the thermal conductivity of the reaction system. As a result, microwave irradiation possesses several unique advantages, such as faster heating rate and obvious reduction in reaction time compared with conventional heating. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…On the other hand, the detected conversion of glycerol was quite low (6.5% at 0.17 h) when conventional heating was selected as the energy supply method, and it climbed to 47.3% within 1.5 h and further increased to 72.8% when the reaction was prolonged to 6 h. These results indicated that microwave irradiation could shorten the reaction time greatly, which might be ascribed to microwave irradiation having higher thermal efficiency thanks to the interaction between the oscillating electromagnetic field of microwave and the dipoles of polar molecules. However, a conventional heating method can only provide heat to the reaction mixture via thermal conduction, and this conduction depends strongly on the thermal conductivity of the reaction system. As a result, microwave irradiation possesses several unique advantages, such as faster heating rate and obvious reduction in reaction time compared with conventional heating. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…Undoubtedly, it is significant to search for renewable and sustainable resources to produce fuels and materials with the aim of lowering the use of fossil fuels and reducing CO 2 emissions. To date, a range of biomass and organic waste including first-, second-, and third-generation biomass have been extensively investigated as the raw materials for the generation of biofuels and biomaterials [1][2][3][4]. Biofuel production obtained from first-generation biomass such as corn is a well-established process; however, it would lead to fuel vs. food competition.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other biomass, hickory shell husk has high hemicelluloses, cellulose, and lignin contents. However, the differences in the structure and reactivity of these major components make the fractionation and utilization of hickory shell [ 4 , 5 ]. In general, cellulose can be hydrolyzed to fermentable sugar for further biofuel production.…”
Section: Introductionmentioning
confidence: 99%